1998
DOI: 10.1093/emboj/17.5.1192
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the tetratricopeptide repeats of protein phosphatase 5: implications for TPR-mediated protein-protein interactions

Abstract: The tetratricopeptide repeat (TPR) is a degenerate 34 amino acid sequence identified in a wide variety of proteins, present in tandem arrays of 3-16 motifs, which form scaffolds to mediate protein-protein interactions and often the assembly of multiprotein complexes. TPR-containing proteins include the anaphase promoting complex (APC) subunits cdc16, cdc23 and cdc27, the NADPH oxidase subunit p67 phox, hsp90-binding immunophilins, transcription factors, the PKR protein kinase inhibitor, and peroxisomal and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
687
1
11

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 778 publications
(713 citation statements)
references
References 43 publications
10
687
1
11
Order By: Relevance
“…TPR repeats are found in proteins with various cellular functions, including cell cycle control, protein transport, and protein dephosphorylation (Blatch and Lassle, 1999). TPR domains participate in protein-protein interactions with TPR-containing and SH2 domain-containing proteins (Das et al, 1998).…”
Section: Disruption Of the Msmile Gene In Mice Resulted In Postnatalmentioning
confidence: 99%
“…TPR repeats are found in proteins with various cellular functions, including cell cycle control, protein transport, and protein dephosphorylation (Blatch and Lassle, 1999). TPR domains participate in protein-protein interactions with TPR-containing and SH2 domain-containing proteins (Das et al, 1998).…”
Section: Disruption Of the Msmile Gene In Mice Resulted In Postnatalmentioning
confidence: 99%
“…The first crystal structure of a TPR protein, a three repeat segment of the PP5 protein phosphatase, was recently solved (Das et al+, 1998)+ The authors of this study (Das et al+, 1998) predict that clustered TPR elements interact to form a right-handed super-helix well suited to act as a platform for the assembly of protein complexes+ Based on its highly repetitive TPR structure and the experimental data presented here, we propose that Clf1p serves as such a multifaceted platform and drives splicing complex assembly by binding multiple spliceosomal proteins+ While unique in its repetitive simplicity, Clf1p serves as a valuable model for how other TPR proteins might punctuate spliceosome assembly through the parallel recruitment of transacting factors to their multiple TPR surfaces+…”
Section: Discussionmentioning
confidence: 99%
“…The Clf1p binding site is within the amino terminus of Prp40p+ Two WW domain elements are present in the amino terminus of Prp40p (Kao & Siliciano, 1996) and have been suggested as possible sites of BBP/SF1 interaction (Abovich & Rosbash, 1997)+ This region of Prp40p is unnecessary for Clf1p interaction, however (Table 1)+ Clf1p does not interact with the isolated WW domain (Prp40p-WW)+ In addition, TPR elements are believed to bind alpha helical surfaces in their target proteins (e+g+, see Tzamarias & Struhl, 1995;Das et al+, 1998), three of which are predicted in the N-terminal half of Prp40p downstream of the WW region+ Removal of the WW domain from the amino half of Prp40p only slightly reduces the level of lacZ reporter gene transactivation when these three helical segments are present (Prp40p-HI, II, III)+ However, deletion of the first of these helices (Prp40p-HII,III), significantly reduces the level of transactivation, suggesting that helix I may form a portion of the Clf1p recognition domain+ Both halves of Clf1p interact with Prp40p, although not as well as the full-length Clf1p+ Presumably Prp40p binds Clf1p through contacts that fall on either side of (and perhaps FIGURE 6. Affinity purification of Clf1p-defective splicing complexes+ Biotin-substituted RP51A (lanes 1-4) or RP51A without biotin (lane 5) was incubated for 45 min under standard splicing conditions in the Clf1p-complete extract (lane 4) or in an extract depleted of Clf1p prior to preparation by transcriptional repression of GAL1::CLF1 (lanes 1-3, 5)+ Splicing complexes (Bound) were recovered by streptavidin chromatography and then assayed by Northern blot for their snRNA contents+ In addition, the total unfractionated snRNA (Total) and the snRNAs remaining unselected after streptavidin chromatography (Unbound) were assayed for the Clf1p-depleted samples+ The location of the spliceosomal snRNAs are indicated by arrow heads on the left+ The high level of reporter gene transactivation suggests, but does not prove, that the interactions of Clf1p with Mud2p and Prp40p are direct+ Additional support for this interpretation is provided by the observation that in vitro-synthesized Mud2p and Prp40p bind a hemagglutinin-tagged version of Clf1p (i+e+, Clf1HAp)+ An antihemagglutinin specific antibody, HA+11, precipitates CLF1HAp but not Mud2p, Prp40p, or a luciferase control protein (Fig+ 8A)+ However, when the in vitro translated proteins are mixed prior to immune precipitation, Mud2p and Prp40, but not the luciferase control coimmune precipitate with the Clf1HAp protein+ The Mud2p/Prp40p/Clf1HAp coprecipitation was maximal at 100 mM NaCl; at 200 mM NaCl, lowered levels of all FIGURE 8.…”
Section: Spliceosome Assembly Is Impeded In the Absence Of Clf1pmentioning
confidence: 99%
“…Rrp5p TPR motifs could be implicated in protein-protein interactions (Lamb et al+, 1995)+ The crystal structure of the TPR repeats was recently resolved (Das et al+, 1998) and revealed a spatial arrangement of one TPR unit in two antiparallel a-helices encompassing the A and B domains reported in Figure 2D+ The a-helices A and B were shown to constitute the inside and outside faces of the TPR repeats respectively, thereby indicating that the conserved residues of the B domain are probably essential residues to mediate protein-protein interactions (Das et al+, 1998)+ The rrp5⌬6 allele encodes a polypeptide deleted for two amino acids in TPR unit 1 (alanine 1494 and arginine 1495) which are conserved residues of the B domain of the TPR motif (Fig+ 2D)+ Therefore, the rrp5⌬6 allele could encode a defective protein-binding factor at restrictive temperature (37 8C) that would be impaired in the recruitment of important component(s) of the maturation process+ As already mentioned, a large number of trans-acting factors other than Rrp5p are required for the same rRNA-processing step (Venema & Tollervey, 1995)+ The Rok1p protein is an attractive candidate to interact with Rrp5p since it was isolated in this study as an extragenic multicopy and low-copy suppressor of the rrp5⌬6 temperature-sensitive mutation, and was also previously isolated with the same synthetic lethality screening used to isolate RRP5 (Venema & Tollervey, 1996;Venema et al+, 1997)+ Rrp5p and Rok1p tightly participate in rRNA processing at step A 2…”
Section: Rrp5d6p May Be a Defective Protein-binding Polypeptidementioning
confidence: 99%